Germany's integration politics in practice: Lived realities of Chinese-speaking skilled female family migrants. (3rd September 2020) - Hsu, Chieh
Abstract: Germany imposes integration-oriented regulations before and after entry on third-country family migrants. However, little attention has been paid to how integration actually unfolds for the subjects of these regulations, usually women, who are situated in the private sphere of the family. This article examines how the concept of integration, a state-anticipated and state-stipulated goal, is connected to the early adaptation of skilled female family migrants who are married to German husbands. Based on participant observation and semi-structured interviews with 21 Chinese-speaking women across Germany, I focus on how these women mobilize resources to overcome 'hurdles' of entry requirements, how they define and interpret their tasks and obligation of integration upon arrival, and how the dynamics of their intercultural marriage affect their integration. Viewing these female spousal migrants as subjects in an integration-oriented family migration regime that legitimates intensive integration also in the private sphere, this article highlights these women's 'wife' and 'migrant' roles in the family. Specifically, through interactions with their significant others and extended family members, role-related expectations are transferred. The results show that female spouses are consequently exposed to an alternative ideal of integration that is tied to their domestic role. This homebound notion of integration differs from the social integration envisioned and coveted by the German government. This research broadly unveils how these skilled female family migrants' early acculturation can be seen as a rivalry between pre-established self-conceptions and new circumstances in the host society.